Methods in the Learning Process: Case Studies on Implementation - Afrizal Afrizal; Rian Vebrianto; Abu Anwar (Buana Pendidikan, 2022)
The learning method is one of the ways used by a teacher or educator to improve learning outcomes for students. Learning methods are in the form of discussions, field trips, and lectures. In general, what is often used by teachers is the lecture method. This method is certainly very boring for students, especially in MI/SD with low grades (1,2, and 3). For this reason, determining learning outcomes can be seen to what extent the teacher is able to manage the class during learning and get maximum results. This research uses descriptive qualitative research. The method used by the researcher is interview, observation and documentation. The results of the interviews are processed into a narrative that can be understood by all readers. The result is that some teachers do not use learning methods optimally. So that learning outcomes are also not expected to be optimal. For this reason, it is up to the school to be able to improve the competence of the educators or teachers in the school.